The Ecological Resilience of Coral Reefs in Pari Island, Jakarta Province - Hadiana; Samosir Agustinus; Zaqi Muhammad (BIO Web of Conferences)
Pari Island located at the Southern part of Thousand Islands Regency in the province of Jakarta, that has experienced environmental damage due to human activities. The objective of this study is to analyse the resilience of the coral reefs in Pari Island. The research was conducted over a period of 8 months, from June 2016 to January 2017. The primary data collection process entailed the utilisation of the LIT (line intercept transect) method for the observation of coral reefs. Secondary data were collected from literature studies related to the environmental conditions. The findings of the study indicated that the coral reef coverage on Pari Island displayed moderate to poor condition. The coral mortality index exhibited a relatively high range, from 0.56 to 0.88. Coral recruitment was observed to be low in the coral reefs of Pari Island. The Porites genus was a dominant feature of the marine ecosystem on Pari Island. In general, the resilience of the coral reefs in Pari Island was moderate to poor. The resistant coral genus was the primary parameter used to determine the resilience of the coral reefs on Pari Island. The coral reefs on Pari Island were classified as part of the resistant category.